Relationship Between the Age of Female Partner and the Intrauterine Insemination Success in Rumah Sakit Ibu dan Anak Puri Bunda Denpasar - Alycia Madeleine; Yukhi Kurniawan; I Gusti Ngurah Pramesemara (Indonesian Andrology and Biomedical Journal, 2022)
Infertility is the inability of couples who have regular sexual intercourse without using protection to achieve pregnancy within one year. The prevalence of infertility was 21.3% in Indonesia. Intrauterine Insemination (IUI) is an assisted reproductive technology chosen by infertile couples to have children. Various factors influence the success of IUI. One factor that influences the success of IUI is the female partner’s age. To determine the relationship between the age of female partners and the success of IUI. This study is descriptive-analytical research with the Cross-Sectional method using secondary data obtained from medical records of patients who underwent IUI procedures from January to March 2020 at Rumah Sakit Ibu dan Anak Puri Bunda Denpasar. Total research subjects are 31 patients with an average age of 32 years. Positive pregnancies in female partners aged 25-35 years are 8 patients (33,3%) and female partners aged 35-40 are 1 patient (14.3%). Most patients had secondary infertility with a duration of 1-3 years. There is no relation between the increasing age of female partners and the decreasing success of IUI at Rumah Sakit Ibu dan Anak Puri Bunda Denpasar (p=0,329). But female partners aged 25-35 years tended to have a positive pregnancy 2,333 times higher than female partners aged 35-40 years (RR=2,333; CI 95%: 0,349-15,612).